Efeitos do ácido gálico em parâmetros bioquímicos e de estresse oxidativo em ratos submetidos a um modelo experimental de diabetes - Oliveira, Lizielle Souza de (2015)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia associated with the increase of free radicals and decrease in the antioxidant response. Gallic acid has many biological properties, among them we can highlight its antioxidant function that can provide a number of benefits for patients with DM. In this context, the aim of this study was to evaluate the treatment effect of gallic acid in biochemical parameters of oxidative stress and histological biomarkers in liver and kidney of diabetic rats induced with streptozotocin. In the present study, we used 40 male Wistar rats were divided into four groups: I - Control II - gallic acid (30mg / kg), III - diabetic IV - Diabetic + gallic acid (30mg / kg). Diabetes mellitus was induced in the animals by intraperitoneal injection of streptozotocin (65 mg / kg). After confirmation of hyperglycemia, began treatment with gallic acid (30mg / kg) which was administered orally for 21 days. After this period the animals were euthanized and blood, liver and kidney were collected for further analysis. The results demonstrated that treatment with gallic acid was able to prevent the formation of reactive species to reduce the levels of lipid peroxidation and increase the activity of superoxide dismutase and delta-aminolevulinic acid dehydratase in the liver and kidney of diabetic rats (P < 0.05) Further, this compound also prevented the decrease in activity of superoxide dismutase, glutathione S-transferase and Vitamin C levels in the livers of diabetic mice (P <0.05). Gallic acid treatment prevented the increase of aspartate aminotransferase activity in liver tissue and reduced the number of nuclei and increased nuclear area, and increased glomerular renal tissue area. These results indicate that the gallic acid may protect against oxidative stress-induced damage in the diabetic state. Therefore, it can be suggested that the gallic acid may be a potential candidate in adjunct therapy in diabetes, due to its antioxidant action, in combination with hypoglycemic drugs.